2011
DOI: 10.1111/j.1752-8062.2011.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Oxidative Stress and Inflammation: In Vitro and In Vivo

Abstract: African American race is an independent risk factor for enhanced oxidative stress and inflammation. We sought to examine whether oxidative‐stress and inflammatory markers that are typically measured in humans also differ by race in cell culture. We compared levels between African American and Caucasian young adults and then separately in human umbilical vein endothelial cells (HUVECs) from both races. We found heightened oxidative stress and inflammation in the African Americans both in vitro and in vivo. Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 29 publications
6
112
1
Order By: Relevance
“…It has been shown that the underlying inflammation or oxidative status might differ among different ethnic groups. A previous study found heightened oxidative stress and inflammation in African Americans both in vitro and in vivo (Feairheller et al 2011). Population-based studies also found that compared to whites, African Americans or Hispanics had higher levels of markers of oxidative stress (Morris et al 2012), lower concentrations of antioxidant alpha-tocopherol (Ford et al 2006), or higher levels of inflammatory markers such as CRP and IL-6 (Kelley-Hedgepeth et al 2008;Paalani et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that the underlying inflammation or oxidative status might differ among different ethnic groups. A previous study found heightened oxidative stress and inflammation in African Americans both in vitro and in vivo (Feairheller et al 2011). Population-based studies also found that compared to whites, African Americans or Hispanics had higher levels of markers of oxidative stress (Morris et al 2012), lower concentrations of antioxidant alpha-tocopherol (Ford et al 2006), or higher levels of inflammatory markers such as CRP and IL-6 (Kelley-Hedgepeth et al 2008;Paalani et al 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Normotensive subjects with a family history of hypertension have greater ROS production than blood pressurematched subjects without a family history of hypertension, suggesting a genetic component that is associated with elevated production of free radicals (57,105,108). Racial differences in oxidative stress and inflammation have also been demonstrated.…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%
“…[7][8][9][10] It has been well-documented in the literature that oxidative stress and inflammation often occur simultaneously and have been linked to endothelial dysfunction and hypertension. [29][30][31] Elucidating the mechanisms relating to inflammation, endothelial dysfunction, and hypertension may be beneficial in developing preventive measures in reducing the CVD risk burden among the African American population.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The high incidence of hypertension in African Americans may be attributed to their predisposition to heightened systemic inflammation. [7][8][9][10] Long-term exposure of the endothelium to proinflammatory cytokines leads to endothelial dysfunction, which supports an environment favoring hypertension. 11,12 It is hypothesized that the intravascular balance between pro-and anti-inflammation plays a crucial role as a determinant of endothelial health.…”
Section: Introductionmentioning
confidence: 99%